Examining the Ethical Considerations of Placing Elderly Parents in Nursing Homes: A Perspective on Maqasid Sharia and Social Welfare - Helim, Abdul; Syarifuddin, Syarifuddin; Suradilaga, Aris Sunandar (Universitas Islam Sultan Agung, 2023)
The objective of this study is to examine the legal status of parental care in juvenile homes, which continues to be a source of contention within the community. Some view the act as an act of disobedience, while others view it from a different perspective. The theoretical framework employed to investigate this issue is the theory maqasid sharia. The rationale for this approach is that it is considered to be a relevant methodology, and no other research has been identified that employs this theory. This type of research is normative legal research, which involves the examination of primary legal materials pertinent to the research. The results of this study indicate that entrusting parents to juvenile homes does not necessarily imply a rupture in the relationship between children and parents. Instead, it allows for the maintenance of positive relations with parents while avoiding the negative consequences of neglecting them. Consequently, this study aligns with maqasid sharia including the protection of parents' lives (hifz al-nafs), enabling parents to focus on worship (hifz al-Din) safeguarding against negative thoughts between them (hifz al-‘aql), pertains to the avoidance of children doing wrong if they gather in the same house (hifz al-Nasl) and encompasses the maintenance of good relations between parents and children as an asset (hifdz al-mal). The results of this study are undoubtedly contentious, particularly when viewed through the lens of divergent trends. Nevertheless, the findings of this study can serve as a reference point to prevent the immediate assumption of unfaithfulness in children who leave their parents in nursing homes.